Tindak Tutur Direktif Dalam Film Lion Of The Desert 1980 (Kajian Pragmatik) - Aldila, Novely (Linguistik : Jurnal Bahasa dan Sastra, 2023)
This study aims to describe the derivative speech act in the 1980 film Lion of Desert. This study used a pragmatic approach. This study used qualitative descriptive method. Researchers took the film Lion Of The Desert as a source of research data. All utterances contained in the Lion Of The Desert film will be the subject of research, while the object of research is all directive speech acts contained in films with the realm of pragmatic studies. The data analysis method used in this study is the equivalent method. This film tells the story of a former teacher, Umar Mukhtar, who is nicknamed the Lion of the Desert for his courage and ability to fight. In 1911 under the leadership of Benito Mussolini, Italy expanded its colonial territory to Libyan territory. In 1929 a war led by Umar Mukhtar broke out. General Benito Mussolini sent General Radofo Garziani with the task of suppressing the rebellion carried out by Umar Mukhtar. From the film Lion Of The Desert (1980) which became the source of this research data obtained dialogues that showed the existence of speech acts that referred to the form and function of directive speech acts. The directive speech acts contained in the film are, orders, requests, advises, prohibitions, invitations, suggestions, begs, questions, indirectly, and directly. While the functions of speech acts contained in the film are: commanding, warning, asking, asking, inviting, and suggestions.